Compact Monocular Video-Ophthalmoscope to Measure Retinal Reflectance Changes to Flicker Light Stimuli - Kolar, Radim; Vicar, Tomas; Chmelik, Jiri; Jakubicek, Roman; Odstrcilik, Jan; Nohel, Michal; Skorkovska, Karolina; Tornow, Ralf-Peter (Journal of Biophotonics, 2025)
This paper describes a compact video-ophthalmoscope (VO) designed for capturing retinal video sequences of the optic nerve head (ONH) under flicker light stimulation. The device uses an OLED display and a fiber optic-coupled LED light source, enabling high-frame-rate video at low illumination intensity (12 μW/cm2). Retinal responses were recorded in 10 healthy subjects during flicker light exposure with a pupil irradiance of 2 μW/cm2. Following 20 s of stimulation, all subjects displayed changes in retinal reflectance and pulsation attenuation, linked to blood flow and volume variations. These findings suggest that increased blood volume leads to decreased retinal reflectance. Temporal analysis confirmed the ability to capture flicker-induced retinal reflectance changes, indicating its potential for spatial and temporal analysis. Overall, this device offers a portable approach for investigating dynamic retinal responses to light stimuli, which can aid the diagnosis of retinal diseases like diabetic retinopathy, glaucoma, or neurodegenerative diseases affecting retinal blood circulation.
CRIS-Team Scopus Importer:2025-04-01
Keywords: blood volume; fundus reflectance; light flickering; neurovascular coupling; optic nerve head; video-ophthalmoscopy